2002
DOI: 10.1007/s00421-002-0621-5
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate loading in human muscle: an improved 1 day protocol

Abstract: It is generally acknowledged that even without a glycogen-depleting period of exercise, trained athletes can store maximal amounts of muscle glycogen if fed a carbohydrate-rich diet for 3 days. What has never been examined is whether under these conditions this many days are necessary for the content of muscle glycogen to attain these high levels. To examine this issue, eight endurance-trained male athletes were asked to eat 10 g.day(-1).kg(-1) body mass of high-carbohydrate foods having a high glycaemic index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(75 citation statements)
references
References 25 publications
1
71
0
3
Order By: Relevance
“…Results indicated that CHO consumption, particularly in the latter half of the week was more important to performance than earlier in the week. This supports the guidelines that shorter CHO loading protocols should be sufficient [29][30]. This is an important message for athletes since they appear to struggle to consume the amounts recommended.…”
Section: Nutrient Intake In the Week Prior To The Eventsupporting
confidence: 75%
“…Results indicated that CHO consumption, particularly in the latter half of the week was more important to performance than earlier in the week. This supports the guidelines that shorter CHO loading protocols should be sufficient [29][30]. This is an important message for athletes since they appear to struggle to consume the amounts recommended.…”
Section: Nutrient Intake In the Week Prior To The Eventsupporting
confidence: 75%
“…In the context of a two game week, it is likely that players did not consume adequate CHO to optimize muscle glycogen storage in the day before and in recovery from the games (Bussau et al, 2002;Krustrup et al, 2006). This point is especially relevant considering the inability to fully replenish muscle glycogen content in type II fibers 48 hr after match play, even when CHO intake is > 8 g·kg -1 body mass per day (Gunnarsson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional carbohydrate loading regimens involve lengthy (7 days) preparations, combining a phase of carbohydrate depletion before high-carbohydrate refueling (Ahlborg et al, 1967). More contemporary research suggests carbohydrate intakes of 10-12 g/kg BM/day for the 36-48 hr before exercise combined with normal training is sufficient to achieve a supercompensation in muscle glycogen stores (Bussau et al, 2002). Female swimmers are encouraged to increase their energy intake in conjunction with carbohydrate intakes to ensure that suitable "loading" occurs (Tarnopolsky et al, 2001).…”
Section: Prerace Nutritionmentioning
confidence: 99%